Role of hereditary factors in weight loss and its maintenance - Hainer, Vojtěch; Zamrazilová, Hana; Spálová, Jana; Aldhoon Hainerová, Irena; Kunešová, Marie; Aldhoon, Bashar; Bendlová, Běla (Physiological research, 2008)
The prevalence of obesity is increasing worldwide at an alarming rate in both developed and developing countries. Obesity is a chronic complex disease of multifactorial origin resulting from a long-term positive energy balance, in which both genetic and environmental factors are involved. Genetically prone individuals are the first to accumulate fat in the present obesogenic environment. Obesity increases the risks of type 2 diabetes, hypertension, cardiovascular disease, dyslipidemia, arthritis, and several cancers and reduces the average life expectancy. Implementation of effective strategies in prevention and management of obesity should become an important target in health care systems. Weight changes throughout life depend on the interaction of behavioral, genetic and environmental factors. Weight loss in response to weight management shows a wide range of interindividual variation which is largely influenced by genetic determinants. The strong control of weight loss by genotype was confirmed by twin and family studies. Recently, special attention has been paid to nutritional, hormonal, psychobehavioral and genetic factors which can predict the response to weight reduction programme. In this article currently available data on the role of obesity candidate gene polymorphisms in weight loss and maintenance are reviewed. It is believed that an elucidation of the genetic component in the prognosis of weight management could assist in the development of more effective and individually tailored therapeutic strategies.
Keywords: Environment; Obesity; životní prostředí; stravovací zvyklosti; Weight Loss; lidé; obezita; Feeding Behavior; Polymorphism, Genetic; polymorfismus genetický; hmotnostní úbytek; Humans